2019
DOI: 10.26434/chemrxiv.11336669
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rationally Designed Long-Wavelength Absorbing Ru(II) Polypyridyl Complexes as Photosensitizers for Photodynamic Therapy

Abstract: The utilization of Photodynamic Therapy (PDT) for the treatment of various types of cancer has gained increasing attention over the last decades. Despite the clinical success of approved photosensitizers (PSs), their application is limited due to poor water solubility, aggregation, photodegradation, and slow clearance from the body. To overcome these drawbacks, research efforts are devoted towards the development of metal complexes and especially Ru(II) polypyridine complexes based on their attractive photophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
(4 reference statements)
0
9
0
Order By: Relevance
“…Importantly, the spectra showed an absorption tail towards the biological spectral window potentially enabling the treatment of deep‐seated and large tumours as the light penetration depth directly correlates with the used wavelengths. Worthy of note, previous studies have shown that PSs can show a phototoxic effect although their extinction coefficients are below 100 m −1 cm −1 . The conjugate was found to have a large Stokes shift, implying minimal interference between excitation and emission.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Importantly, the spectra showed an absorption tail towards the biological spectral window potentially enabling the treatment of deep‐seated and large tumours as the light penetration depth directly correlates with the used wavelengths. Worthy of note, previous studies have shown that PSs can show a phototoxic effect although their extinction coefficients are below 100 m −1 cm −1 . The conjugate was found to have a large Stokes shift, implying minimal interference between excitation and emission.…”
Section: Resultsmentioning
confidence: 76%
“…To tackle this issue, some of us have recently reported the DFT‐guided design of Ru II polypyridine complexes with a strong absorption red shift towards the biological spectral window (600–900 nm). In this pursuit, the complex [Ru(4,7‐diphenyl‐1,10‐phenanthroline) 2 (4,4′‐dimethyl‐2,2′‐bipyridine)] 2+ , which showed a phototoxic effect from 480 nm up to clinically relevant 595 nm, was unveiled …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, much efforts are devoted towards the development of transition metal complexes as PDT PSs. 40 The majority of complexes studied are based on Ru(II), [41][42][43][44][45][46][47][48][49][50][51] Os(II), [52][53][54] Ir(III), [55][56][57][58][59][60][61] Rh(III) [62][63][64] and Re(I). [65][66][67][68][69] As these metals are expensive, it would be of high interest to develop PSs based on cheap, abundant metals.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure S11, Supporting Information, at the buffer solution with pH 6.8, the absorption of the ABDA in the presence of BT-Ir decreased significantly within 2 min, indicating highly efficient ROS generation in the acidic environment, which is more conducive to kill cancer cells as the tumor microenvironment is acidic. [15] Although 1 O 2 (type II) is considered to be the predominant primary ROS involved in PDT, there is growing evidence that other ROS (type I, including superoxide anion (O 2 − ), hydroxyl radical (HO • ), hydrogen peroxide (H 2 O 2 ), etc. ), may also be produced during the PDT process and play important roles in cell death.…”
Section: Resultsmentioning
confidence: 99%
“…Photodynamic therapy (PDT) involves the production of reactive oxygen species (ROS) by the irradiation of photosensitizers (PSs), which is considered as one of the most momentous strategies to eliminate cancer cells with minimal invasiveness and precise spatiotemporal selectivity. [1][2][3][4] The primary cytotoxic agents involved in this photodynamic process are reactive oxygens, such as singlet oxygen ( 1 O 2 ), hydroxyl radicals (OH • ), etc. [5,6] The incorporation of heavy atoms into the molecular structures is one of the widely used approaches to improve the ROS yield of PSs.…”
Section: Introductionmentioning
confidence: 99%